The someday garden - Poston, Ashley (Berkley, 2026)
"The new head gardener at the enchanting Lilymoor House stumbles upon a secret garden ... with a mysterious man trapped inside, in the next magical novel from the New York Times bestselling author of Sounds Like Love and The Seven Year Slip. When Sophie Drear plans her escape to coastal Maine for the summer-for a temporary job revitalizing the storied grounds at Lilymoor House-she doesn't expect to fall in love. But she does: With the beguiling land, the fragrant flowers, and the towering hedge maze. With the quirky staff and the enigmatic woman who owns the place. And then, the door appears. Never in the same place twice, it leads her to a secret, and unfinished, garden with a frustrated thundercloud of a man trapped inside. This mysterious garden is not the only sign that the future of Lilymoor is unstable: the foliage resists Sophie's careful nurturing, vines threaten to strangle the hedges, and the manor's owner has wild ideas about who will take over when she retires-including her inconveniently attractive nephew who is also there just for the summer. Despite herself, Sophie has come to care for the residents of Lilymoor just as much as she cares for its grounds. With the help of one man on the outside of the secret garden, and one man on the inside, she might be the only person who can figure out exactly what Lilymoor needs to bloom once more"-- Provided by publisher.